Varicella pneumonia in an immunocompetent adult patient: Case report and review of the literature - Carlos Felipe Arias-Osorio; Heiler Lozada-Ramos; Jorge Enrique Daza-Arana; Luis Miguel Osorio-Toro; Diana Marcela Bonilla-Bonilla (Respiratory Medicine Case Reports)
Varicella is a childhood disease characterized by its self-limiting and benign nature. However, it can also affect the adult population due to risk factors, leading to infection with numerous complications involving the central nervous system, kidneys, respiratory system, and skin. Varicella pneumonia, one of the most feared complications in adults, occurs in approximately 1 out of 400 patients with the disease. This complication primarily affects male patients with a history of heavy smoking and immunosuppression, either due to an underlying disease such as HIV and cancer, drug use, pregnancy or pulmonary disease. It is recommended that this complication should be treated with intravenous acyclovir at a dose of 10 mg/kg/8 hours. The prognosis depends on the development of respiratory failure; up to 50 % of patients with this complication require invasive mechanical ventilation. Here, we report the clinical case of an immunocompetent patient with a typical presentation of varicella that rapidly progressed to a respiratory infection requiring antiviral treatment and invasive mechanical ventilation.